Bioelectricity Generation From Mixture Of Palm Oil Mill Effluent And Wet Palm Oil Sludge By Using Graphite Rod As Electrode In Microbial Fuel Cell - Nurul Izyan, Ismail (2022)
A dual chamber microbial fuel cell (MFC) was constructed to study the potential of palm oil mill effluent (POME) as substrate and wet palm oil sludge (WPOS) as additive to generate electricity. Various amount of dosage which is 0 mg/L, 2mg/L, 4 mg/L and 6 mg/L of WPOS was added to mix with the POME. The duration of MFC operation was 20 days which 5 days for each dosage of WPOS. Graphite rod was used as electrode throughout the MFC operation. The MFC operation using mixture from POME with 4 mg/L dosage of WPOS show a maximum power which is 9.17 x 10-6W. The maximum power achieved in second day of MFC operation. The factors that effecting the performance of MFC was determined. Total suspended solid (TSS), chemical oxygen demand (COD) and pH showed the effect towards the MFC performance. The highest percent of COD removal was 21% which indicate the effectiveness of MFC. Operating parameter which is WPOS as additive and operational time was identified in this study. 4 mg/L dosage of WPOS as additive in MFC showed the highest power production throughout the operation. The high power for each 0 mg/L, 2mg/L, 4 mg/L and 6 mg/L was achieved in second day of their operation. The result indicates that MFC succeeded show the potential of electricity generation from the mixture of POME an WPOS using graphite as electrode. Besides that, operating parameter, TSS, COD and pH indicate the great influence in MFC performance.